Determinan dan Strategi Penumbuhan Klaster Bisnis Koperasi - Caska, C (Jurnal Trikonomika, 2011)
This research is purposed to (1) describe the growing of cooperative business cluster; (2) the factors are determining the growing of cooperative business cluster; (3) development strategy of cooperative business cluster. This research used descriptive method. The results shows: first, the leading bisnis sector of cooperative business clusters are planting palm, trading of basic needs and input goods, credit, transportation, and CPO factory. Second, determining factors of cooperative business cluster growing are innovation of member; low cost and differentiation product; competitive price and specialization; and displacement. Third, development strategy of cooperative business cluster are market driven, inclusive, collaborative, strategic, value creating, and government policy.